Implementasi Metode Belajar dan Bermain Melalui Program Arabic Center Kids dalam Meningkatkan Kemampuan Bahasa Arab Santri TPQ Misbachur Rochman Tambak Sari Waru Sidoarjo - Mufaizah Mufaizah; Moch. Ikwan; Amalia Salsabilla; Cholifatul Azizah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2024)
Arabic has an important position as the language of science and the language of the Qur'an that needs to be introduced early on, especially amidst the challenges of globalization that affect the use of foreign languages ​​in everyday life. However, learning Arabic is still considered difficult, especially by children. This article aims to describe the implementation and impact of the Arabic Center Kidz program designed to introduce Arabic through fun and interactive methods at TPQ Misbachur Rochman, Dusun Tambak Sari, Sidoarjo. This study uses a descriptive qualitative approach with stages of assessment, preparation, implementation, and evaluation. The learning methods used include Shaw and Tell, singing and memorizing, muhadatsah, and language games (al-Lu'bah al-Lughawiyah). The results of the study showed an increase in participants' ability to understand and pronounce Arabic vocabulary as well as growing interest and self-confidence in the learning process. The conclusion of this study is that Arabic learning can be done effectively with a contextual, fun, and sustainable approach